THE IMPACT OF COMMUNITY INTEREST IN SENDING CHILDREN TO IBTIDAIYAH MADRASAH ON THE REDUCTION IN THE NUMBER OF ELEMENTARY SCHOOLS IN PONOROGO REGENCY - Mukhlison Effendi; Galih Akbar Prabowo (IAIN PONOROGO, 2022)
Penurunan jumlah SD dari tahun 2015 hingga tahun 2019 di Kabupaten Ponorogo sebanyak 12 sekolah dalam waktu 5 tahun. Terdapat kenaikan sebanyak 14 sekolah MI dalam waktu 5 (2015-2019) tahun di Kabupaten Ponorogo.Faktor-faktor yang mempengaruhi minat masyarakat untuk menyekolahkan anak di MI adalah faktor ketertarikan, perasaan senang dan perhatian. Nilai signifikan dari hasil perhitungan regresi menunjukkan angka 0,000<0,05 sehingga H0 ditolak. Nilai signifikan yang kurang dari 0,05 menunjukkan hasil bahwa ada pengaruh persepsi orang tua terhadap minat orang tua untuk menyekolahkan anaknya di MI. [Decreasing the number of elementary schools from 2015 to 2019 in Ponorogo District was 12 schools in 5 years. There has been an increase of 14 MI(Madrasah Ibtidaiyah) in 5 (2015-2019) years in Ponorogo Regency. Factors affecting the community's interest in sending children to MI are factors of interest, feelings of pleasure and attention. Significant value of the results of the regression calculation shows the number 0,000 <0.05 so that H0 is rejected. Significant value of less than 0.05 indicates the result that there is an influence of parental perceptions of parents' interest in sending their children to MI.]